Brain injury markers in blood predict signs of hypoxic ischaemic encephalopathy on head computed tomography after cardiac arrest - Lagebrant, Alice; Lang, Margareta; Nielsen, Niklas; Blennow, Kaj; Dankiewicz, Josef; Friberg, Hans; Hassager, Christian; Horn, Janneke; Kjaergaard, Jesper; Kuiper, Mikael A.; Mattsson-Carlgren, Niklas; Pellis, Tommaso; et al. (Resuscitation, 2023)
Signs of hypoxic ischaemic encephalopathy (HIE) on head computed tomography (CT) predicts poor neurological outcome after cardiac arrest. We explore whether levels of brain injury markers in blood could predict the likelihood of HIE on CT. Retrospective analysis of CT performed at 24–168 h post cardiac arrest on clinical indication within the Target Temperature Management after out-of-hospital cardiac arrest-trial. Biomarkers prospectively collected at 24- and 48 h post-arrest were analysed for neuron specific enolase (NSE), neurofilament light (NFL), total-tau and glial fibrillary acidic protein (GFAP). HIE was assessed through visual evaluation and quantitative grey-white-matter ratio (GWR) was retrospectively calculated on Swedish subjects with original images available. In total, 95 patients were included. The performance to predict HIE on CT (performed at IQR 73–116 h) at 48 h was similar for all biomarkers, assessed as area under the receiving operating characteristic curve (AUC) NSE 0.82 (0.71–0.94), NFL 0.79 (0.67–0.91), total-tau 0.84 (0.74–0.95), GFAP 0.79 (0.67–0.90). The predictive performance of biomarker levels at 24 h was AUC 0.72–0.81. At 48 h biomarker levels below Youden Index accurately excluded HIE in 77.3–91.7% (negative predictive value) and levels above Youden Index correctly predicted HIE in 73.3–83.7% (positive predictive value). NSE cut-off at 48 h was 48 ng/ml. Elevated biomarker levels irrespective of timepoint significantly correlated with lower GWR. Biomarker levels can assess the likelihood of a patient presenting with HIE on CT and could be used to select suitable patients for CT-examination during neurological prognostication in unconscious cardiac arrest patients.